West Nile Virus Seroprevalence and Behavioral Risks in HIV-1 Infected Individuals, Northern Greece, 2011. (January 2015) - Pilalas, Dimitrios; Skoura, Lemonia; Metallidis, Simeon; Kourelis, Andreas; Tsachouridou, Olga; Malisiovas, Nicolaos; Papa, Anna
Highlights: We conducted a WNV seroprevalence study in HIV patients in Northern Greece. The patient population was surveyed for behavioral risks for WNV infection. The WNV seroprevalence is 1.2% among native HIV patients in northern Greece. Approximately half of the patients were not aware of WNV prevention measures. Approximately half of the patients implemented at least 3 prevention measures. Summary: Objectives: This study sought to assess the West Nile Virus (WNV) seroprevalence and behavioral risk factors for WNV infection in HIV-1 infected individuals in Northern Greece in 2011. Methods: We prospectively enrolled 91 HIV-1 consecutive patients followed up in the HIV clinic of the AHEPA University Hospital in the period from November to December 2011. Serum samples were tested for the presence of WNV IgG antibodies. All subjects were administered a standardized questionnaire to evaluate for risk factors for WNV infection. Results: WNV IgG antibodies were detected in three subjects (3.3%, 95% CI 0.7-9.3%), two of whom were of African origin. The prevalence of WNV antibodies in HIV patients of Greek origin was 1.2% (95% CI: 0.03% - 6.3%). In the sample surveyed, 53.6% (95% CI: 42.4% to 64.5%) were aware of WNV prevention measures; 2.2% reported no implementation of prevention measures, whereas 46.1% implemented at least three measures. Approximately one half of the patients reported outdoor activities for more than two hours from dusk to dawn. None of the IgG-positive patients reported any symptoms compatible with WNV disease during the season at risk. Conclusions: Among native Greek HIV patients, the WNV seroprevalence is 1.2%. A considerable proportion of patients was aware of WNV prevention measures and implemented some of these. HIV patients and other categories of immunocompromised patients are at increased risk of neuroinvasive disease, and widespread implementation of prevention measures should be strongly encouraged in this patient population.